Effects of Voluntary Running Wheel Exercise-Induced Extracellular Vesicles on Anxiety - Yoon, Kyeong Jin; Park, Suhong; Kwak, Seung Hee; Moon, Hyo Youl (Frontiers in Molecular Neuroscience, 2021)
Anxiety disorders are the most frequently diagnosed psychological condition, associated with serious comorbidities including excessive fear and interference with daily life. Drugs for anxiety disorders are typically prescribed but the side effects include weight gain, nausea, and sleepiness. Exercise is an effective treatment for anxiety. Exercise induces the release of extracellular vesicles (EVs) into the circulation, which transmit signals between organs. However, the effects of exercise-induced EVs on anxiety remain poorly understood. Here, we isolated EVs from the sera of mice that were sedentary or that voluntarily exercised. We characterized the changes in the miRNA profile of serum EVs after 4 weeks of voluntary exercise. miRNA sequencing showed that 82 miRNAs (46 of which were positive and 36 negative regulators) changed after exercise. We selected genes affected by at least two miRNAs. Of these, 27.27% were associated with neurotrophin signaling (9.09% with each of central nervous system neuronal development, cerebral cortical cell migration, and peripheral neuronal development). We also analyzed behavioral changes in mice with 3 weeks of restraint stress-induced anxiety after injection of 20 µg amounts of EVs from exercised or sedentary mice into the left cerebral ventricle. We found that exercise-derived EVs reduced anxiety (compared to a control group) in a nest-building test but found no between-group differences in the rotarod or open field tests. Exercise-derived EVs enhanced the expression of neuroactive ligand-receptor interaction genes. Thus, exercise-derived EVs may exhibit anti-anxiety effects and may be of therapeutic utility.